Some suggestions for Turkey within the scope of outdoor education success of new zealand - Okur Berberoğlu, Emel (Journal of Turkish Science Education, 2015)
Outdoor education is evaluated a complementary component of the formal education. New Zealand is one of the most successful countries in terms of outdoor education. Therefore the author conducted interviews with three people who have been working at the outdoor education foundations in New Zealand. The aim of this study is to determine how New Zealand is successful at outdoor education and what Turkey can do in order to improve outdoor education. Qualitative approach and semi-structured interview were used in this research. 14 questions were prepared according to two main points. One of them was Taba-Tyler Model. The other point was intuitional management. 2 themes and 8 codes were determined at the end of the evaluations. The themes were named ‘programme development and management’. There were four codes under programme development: aim, content, learning experiences, evaluation. There were four codes under management: staff, collaboration and professional development of teachers, first aid, and expenditure. Turkey realizes the importance of outdoor education and funds some outdoor education via TUBITAK but this is not enough. Outdoor education in Turkey needs to be institutionalisation. This is important to get sustainability of outdoor education.